2018
DOI: 10.1111/clr.13381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the keratinized mucosa on the stability of peri‐implant tissues and brushing discomfort: A 4‐year follow‐up study

Abstract: Objective The purpose of the present prospective follow‐up study was to evaluate the long‐term influence of the peri‐implant keratinized mucosa (KM) on marginal bone level (MBL), peri‐implant tissues health, and brushing discomfort. Material and Methods Eighty patients were initially recruited during their maintenance visit from January to October 2013 and allocated in two groups according to KM width around implants: Wide Group (KM ≥ 2 mm) and Narrow Group (KM < 2 mm). In the four‐year follow‐up examination (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
185
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 35 publications
(64 reference statements)
6
185
1
14
Order By: Relevance
“…Few subjective symptoms were observed in this study while other studies stated that higher brushing discomfort was reported from patients with implants displaying <2 mm KM (Perussolo, Souza, Matarazzo, Oliveira, & Araújo, 2018; Roccuzzo, Grasso, & Dalmasso, 2016). Seven subjects in the no‐surgery group did not want the study intervention (FGG) because they did not experience any discomfort during the course of the study or even before the study.…”
Section: Discussioncontrasting
confidence: 52%
“…Few subjective symptoms were observed in this study while other studies stated that higher brushing discomfort was reported from patients with implants displaying <2 mm KM (Perussolo, Souza, Matarazzo, Oliveira, & Araújo, 2018; Roccuzzo, Grasso, & Dalmasso, 2016). Seven subjects in the no‐surgery group did not want the study intervention (FGG) because they did not experience any discomfort during the course of the study or even before the study.…”
Section: Discussioncontrasting
confidence: 52%
“…Adequate (usually ≥ 2mm) soft tissue thickness and keratinized mucosa width have been reported to lead to healthier peri‐implant soft and hard tissues (Grischke et al, ), as well as to promote less bone loss, improved oral hygiene (Perussolo et al, ), and better mucosal esthetics (Bonino et al, ). A subanalysis performed in the present study revealed that VMT <2 mm did not affect the bone remodeling around equi‐ and subcrestal implants since no statistically significant difference was found.…”
Section: Discussionmentioning
confidence: 99%
“…Peri‐implantitis is characterized by a non‐linear and accelerating pattern of peri‐implant marginal bone loss (Derks et al, ), where a lack of KM has been suggested to contribute towards the onset of peri‐implantitis (Gobbato et al, ; Lin et al, ). In fact, a very recent prospective follow‐up study demonstrated that KM width and time in function had a statistically significant effect on MBL (Perussolo, Souza, Matarazzo, Oliveira, & Araujo, ). This was supportive of previous findings (Zigdon & Machtei, ).…”
Section: Discussionmentioning
confidence: 99%